2013
DOI: 10.1007/s00198-013-2476-5
|View full text |Cite
|
Sign up to set email alerts
|

Milk consumption throughout life and bone mineral content and density in elderly men and women

Abstract: Summary Association between bone mineral density and bone mineral content in old age and milk consumption in adolescence, midlife, and old age was assessed. The association was strongest for milk consumption in midlife: those drinking milk daily or more often had higher bone mineral density and content in old age than those drinking milk seldom or never. Introduction The role of lifelong milk consumption for bone mineral density (BMD) and bone mineral content (BMC) in old age is not clear. Here we assess the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 38 publications
0
11
0
1
Order By: Relevance
“…However, according to Dwyer & Coleman ( 44 ) , foods with special characteristics (such as cod liver oil), can be recalled particularly well, and the question on midlife cod liver oil intake showed the highest validity of any food item in our FFQ. Also, midlife milk intake, an important covariate in the present study, was among the foods showing the highest correlation in validation studies of the FFQ ( 14 , 15 , 24 ) . Another limitation is that, although the most common portion of cod liver oil is the recommended spoonful, we did not have access to the absolute amount consumed.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…However, according to Dwyer & Coleman ( 44 ) , foods with special characteristics (such as cod liver oil), can be recalled particularly well, and the question on midlife cod liver oil intake showed the highest validity of any food item in our FFQ. Also, midlife milk intake, an important covariate in the present study, was among the foods showing the highest correlation in validation studies of the FFQ ( 14 , 15 , 24 ) . Another limitation is that, although the most common portion of cod liver oil is the recommended spoonful, we did not have access to the absolute amount consumed.…”
Section: Discussionmentioning
confidence: 53%
“…Fish intake has also decreased considerably, which has resulted in minimal changes in vitamin A and D intake, as lean fish containing minimal amounts of these vitamins constituted about 80 % of total fish intake ( 22 , 23 ) . Changes in milk intake are mirrored in our AGES-FFQ data ( 24 ) .…”
Section: Discussionmentioning
confidence: 55%
“…In addition, calcium is necessary for the natural mineralization of the bones and the matrix of cartilage [4]. According to the evidence, calcium can also reduce the risk of osteoporosis in the older population [5][6][7][8]. In adulthood, consuming dairy is associated with the risk reduction for some chronic diseases [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown benefits of dairy food consumption on bone health, reporting positive relationship between calcium intake and bone mineral density (BMD) (8-13); however, there are studies who did not find any consistent evidence on bone health (14-16). …”
Section: Introductionmentioning
confidence: 99%
“…Among many established risk factors of osteoporosis, nutritional factors offer particular opportunity for intervention ( 5 - 7 ). Numerous studies have shown benefits of dairy food consumption on bone health, reporting positive relationship between calcium intake and bone mineral density (BMD) ( 8 - 13 ); however, there are studies who did not find any consistent evidence on bone health ( 14 - 16 ).…”
Section: Introductionmentioning
confidence: 99%